Question #43077

1 Answer
Apr 27, 2017

Answer:

See the entire solution process below:

Explanation:

The slope-intercept form of an equation is: #y = color(red)(m)x + color(blue)(b)#

Where: #color(red)(m)# is the slope of the line and #color(blue)(b)# is the y-intercept of the line.

We can substitute the values of the point from the problem for #x# and #y# and the slope for the problem for #m# and solve for #b#:

#y = color(red)(m)x + color(blue)(b)# becomes:

#-3 = (color(red)(-1) * 4) + color(blue)(b)#

#-3 = -4 + color(blue)(b)#

#color(red)(4) - 3 = color(red)(4) - 4 + color(blue)(b)#

#1 = 0 + color(blue)(b)#

#1 = color(blue)(b)#

We can now substitute the slope from the problem and the y-intercept we calculated into the slope-intercept formula to write the equation:

#y = color(red)(-1)x + color(blue)(1)#